Analyzing the effect of physical activity on cyberattack behavior in college students using the chain mediation model - Zhao, Hongbo; Chen, Bo (Frontiers in Psychology, 2025)
IntroductionCyberattack behavior is an undesirable phenomenon among college students in China that cannot be ignored, and it has always been under the close scrutiny of researchers. This study investigated and analyzed 536 college students using the Physical Activity Rating Scale, the Cyber Aggressive Behavior Scale, the Moral Excuse Scale, and the Rumination Thinking Scale. The aim was to explore the mediating effect of moral excuses and rumination thinking on the relationship between physical activity and cyberattack behavior in college students.Findings(1) Physical activity, moral excuses, rumination thinking, and cyberattack behavior among college students are correlated in pairs. (2) Physical activity negatively predicted moral excuses and cyberattack behavior as well as rumination thinking. Moral excuses positively predicted rumination thinking and cyberattack behavior while rumination thinking positively predicted cyberattack behavior.ConclusionMoral excuses and rumination thinking both individually and chain-mediate the relationship between physical activity and cyberattack behavior among college students.